Macroprudential supervision: From theory to policy - Dirk Schoenmaker; Peter Wierts (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2016)
Financial supervision focuses on the aggregate (macroprudential) in addition to the individual (microprudential). But an agreed framework for measuring and addressing financial imbalances is lacking. We propose a holistic approach for the financial system as a whole, beyond banking. Building on our model of financial amplification, the financial cycle is the key variable for measuring financial imbalances. The cycle can be curbed by leverage restrictions that might vary across countries. We make concrete policy proposals for the design of macroprudential instruments to simplify the current framework and make it more consistent.
Keywords: E44; G01; G28; 330; financial cycle; macroprudential policy; financial supervision; leverage ratio